Study of the modification mechanism and high-temperature rheological properties of OMMT/SBS-modified asphalt - Yi, Qiang; Zhang, Zhenghao; Tan, Shengrui; Peng, Chunhong; Rong, Hongliu (Frontiers in Materials, 2025)
This study systematically investigates the effects of two types of organic montmorillonite (OMMT-F and OMMT-C) on the physical and high-temperature properties of styrene-butadiene-styrene (SBS) modified asphalt to clarify the underlying modification mechanism. Through a combination of physical tests, Dynamic Shear Rheometer (DSR) analysis, Fluorescence Microscopy (FM), Fourier-Transform Infrared Spectroscopy (FTIR), and Atomic Force Microscopy (AFM), the results show that while OMMT content below 3% does not significantly impact flexibility, a 5% content of OMMT-F reduces penetration and ductility more severely than OMMT-C. Both OMMT types enhance high-temperature performance, as evidenced by an increased softening point and rutting factor, with FM revealing that OMMT promotes asphaltene agglomeration and AFM identifying a reinforcing honeycomb structure on the asphalt surface. FTIR analysis confirms that this modification is primarily a physical process. Collectively, these findings provide a comprehensive microscopic-level comparison of OMMT types, offering valuable insights for optimizing SBS modified asphalt and presenting significant research value and practical implications for pavement engineering.